Titanium elastic nails vs locking plate in pediatric subtrochanteric femur fractures: A systematic review and meta-analysis - Zhang, Yaqiang; Xue, Yun; Zhao, Maosheng; Chen, Xianxia; Gao, Qiuming (Frontiers in Pediatrics, 2023)
Objective Titanium elastic nails (TENs) and locking plates (LPs) are currently the main internal fixation for treating pediatric subtrochanteric femur fractures, and the optimal choice of internal fixation is controversial. This study aimed to systematically evaluate the effectiveness and safety of TENs and LPs in treating subtrochanteric fractures in children to provide a theoretical basis and reference for clinical treatment. Methods The literature related to TENs and LPs for treating subtrochanteric fractures in children was searched using the CNKI, PubMed, Cochrane, Embase, and Web of Science, and the search time frame was from the establishment of the database to October 2022. Two evaluators screened the literature according to the inclusion and exclusion criteria and extracted relevant data. Meta-analysis was performed using Stata14.0 software. Results A total of 9 studies with 407 patients with subtrochanteric femur fractures were included in the final screening, including 210 cases with TENs and 197 cases with LPs. Meta-analysis results showed that compared with the locking plate, TEN had a shorter operative time [WMD = −1.3, 95%CI(−1.94,-0.66), p < 0.01], less intraoperative bleeding [WMD = −84.45, 95%CI(−111.09, −57.82), p < 0.01], shorter fracture healing time [WMD = −1.3, 95%CI(−1.94,−0.66), P < 0.01], shorter hospital stays [WMD = −2.80, 95% CI(−4.63,−0.98), p < 0.01], and earlier full weight bearing [SMD = −0.48, 95% CI(−0.91,−0.04), p < 0.05] but more intraoperative fluoroscopy [WMD = 28.23, 95% CI(15.22,41.25), p < 0.05]. The overall complication rate was high [OR = 3.52, 95% CI(1.96,6.34), p < 0.05], and the postoperative period was prone to angulation, rotation, and inversion deformity [OR = 3.68, 95% CI(1.40, 9.68), p < 0.05]. No significant difference in the incidence of lower limb inequality between the two types of internal fixation [OR = 0.83, 95% CI(0.38, 1.85), p > 0.05] and no significant difference in the Harris score of the hip at the last follow-up between the two types of internal fixation [WMD = −0.67, 95% CI(−2.01,0.67), p > 0.05] were found. Conclusion In comparison to LPs, TENs have a shorter operation time, less intraoperative bleeding, and a shorter fracture healing time, and the child can be fully weight-bearing earlier. Locking plates can reduce the operator's x-ray exposure, and the incidence rate of postoperative angulation, rotation, and inversion deformity is low. Therefore, TENs and LPs are the best internal fixation methods for treating subtrochanteric fractures in children.